Initial Oral English Communication Needs of Learners in the Business English Classroom - Paramudia Paramudia; Hadina Habil (Intelektual Pustaka Media Utama, 2015)
The aim of the study was to investigate the level of effectiveness and initial oral English communication (OEC) needs of Indonesian learners when using OEC to perform the learning activities in the Business English (BE) classroom at Business Administration Departement of the Politeknik Negri Ujung Pandang (PNUP) in Makassar Indonesia. Conceptually, the needs of learners cover aspect of